The capabilities for implementing key account management: a systematic review - Sun, Liang; Marcos Cuevas, Javier; Prior, Daniel (American Marketing Association, 2022)
Purpose – To identify the capabilities that facilitate KAM Implementation Design/methodology/approach –A systematic review of 90 studies published from 1990 through to 2021 is conducted. A descriptive analysis and a thematic synthesis are presented. Findings – The paper draws a distinction between KAM formulation and implementation. A framework is developed that classifies the resources and capabilities as tangible and intangible resources, operational, relational, and dynamic capabilities. Originality/value –This study refines previous classifications of tangible and intangible KAM resources and identifies relational capabilities as uniquely related to KAM implementation.
Keywords: Key account management; Resource-based view; Dynamic capabilities